Survei Studi tentang Kebugaran Jasmani Siswa Kelas V di SD Negeri 060857 Medan Tembung - Steven Parningotan Pardede; Samsuddin Siregar; Muhammad Arif; El Roy Gulo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to increase the physical fitness level of class V students at SD Negeri 060857 Medan Tembung. The method used is a survey measuring physical fitness through standard tests. The results showed that the majority of students were in the moderate to poor fitness category, with some students requiring more attention in the fitness aspect. It is hoped that these findings can become a basis for improving sports programs in schools.